Measuring adherence to unsupervised, conservative treatment for knee osteoarthritis: A systematic review - Duong, V; Daniel, MS; Ferreira, ML; Fritsch, CG; Hunter, DJ; Wang, X; Wei, N; Nicolson, PJA (Elsevier, 2021)
Objective To describe the measurement of adherence to unsupervised, conservative treatments for knee osteoarthritis (OA), including the methods of adherence measurement, parameters for assessing adherence and any values used to quantify adherence.